Building core competencies in a turbulent environment - Tan, Justin (Managing global transitions, 2006)
The impact of firm resources and capabilities on performance among Chinese enterprises has been a subject of anecdotal speculation due to its significant implications for organizational researchers as well as practitioners. Yet empirical evidence has been very limited. In this research, set in the People`s Republic of China, we examine firm resources and capabilities and their impact on firm performance among Chinese enterprises. Using large sample of 12,047 Chinese firms from 1991 to 1992, we found that most of the firm specific resources and capabilities examined in this study have a positive impact on performance. We discussed the implications for organiyational researchers, policy makers, and managers, and proposed directions for future research.
Keywords: Kitajska; tranzicija; ekonomski razvoj; strategija razvoja; podjetništvo